O dueto cômico: da Commédia dell'arte ao cavalo marinho - Santos, Ivanildo Lubarino Piccoli dos [UNESP] (2015)
This thesis is based on the identification and comparative analysis of comedic double present in the Commedia dell'Arte italian and the manifestation of brazilian popular culture Cavalo Marinho and refers to the pairs of circus clowns. There are many common traits in these scenic manifestations, such as the characteristics and functions of comic archetypes popular present in them. Initially, it presented an understanding of the origins, formation and characteristics of comedic double based on the historical and artistic context of its emergence, the elements of its structure, its function and its perma nence over time, demonstrating some of its main representatives.The analysis takes as its starting point the trickster myth, whose definition enables understanding of the dualities that arise in performing demonstrations. It is then traced a historical course of the Commedia dell'Arte, to get the two comedic archetypal poles represented by First and Second Zanni, Brighella and Arlecchino, respectively, their icons representatives. The final part is devoted to a study of the Cavalo Marinho, author of the master object, focused especially on the relationship of double comedic Mateus and Bastião